Development and experimental validation of an acid mine drainage prediction tool based on mineral particles - Ramatsoma, Mafeni Samuel (University of the Witwatersrand, Johannesburg, 2024)
Acid Mine Drainage (AMD) is an environmental hazard that is generated as a by-product of mining-related activities. It is an acidic metal-rich water formed when sulfide minerals react with oxygen and water. Due to different ore types at different mines, kinetic AMD models are often ‘calibrated’ with kinetic humidity tests done with the target mine site ore. However, most of these tests require several months to complete. This study aimed to investigate ways to reduce the time required to conduct kinetic humidity tests, and to develop a mineral particles-based kinetic AMD model. An Accelerated Humidity Cell (AHC) is proposed in this study. It was tested with two ore types and performed better (produced 24% more acidic-leachates) than normal humidity cells. The particles-based model was developed and tested with experimental data and gave promising results. It is recommended that the proposed model and AHC be further tested with other ore types.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; AMD Prediction; kinetic tests; accelerated humidity cell; SDG-7: Affordable and clean energy